2021
DOI: 10.1126/sciadv.abf0269
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh-yield on-surface synthesis and assembly of circumcoronene into a chiral electronic Kagome-honeycomb lattice

Abstract: On-surface synthesis has revealed remarkable potential in the fabrication of atomically precise nanographenes. However, surface-assisted synthesis often involves multiple-step cascade reactions with competing pathways, leading to a limited yield of target nanographene products. Here, we devise a strategy for the ultrahigh-yield synthesis of circumcoronene molecules on Cu(111) via surface-assisted intramolecular dehydrogenation of the rationally designed precursor, followed by methyl radical-radical coupling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 55 publications
0
48
0
Order By: Relevance
“…The synthetic procedures of the HPB and F-HPB compounds have been reported in previous studies. , A Knudsen cell was used to deposit the HPB and F-HPB precursor molecules (at 160 and 180 °C, respectively) onto a Ag(111) surface held at room temperature. The STM experiments were performed in ultrahigh vacuum conditions (base pressure of >5 × 10 –11 mbar) at 4.4 K using a commercial Omicron low temperature STM system.…”
Section: Methodsmentioning
confidence: 99%
“…The synthetic procedures of the HPB and F-HPB compounds have been reported in previous studies. , A Knudsen cell was used to deposit the HPB and F-HPB precursor molecules (at 160 and 180 °C, respectively) onto a Ag(111) surface held at room temperature. The STM experiments were performed in ultrahigh vacuum conditions (base pressure of >5 × 10 –11 mbar) at 4.4 K using a commercial Omicron low temperature STM system.…”
Section: Methodsmentioning
confidence: 99%
“…As visualized by STM and nc-AFM, the coupling of methyl groups proceeded when heated to 350°C, mainly forming the ethanediyl bridges alongside fully conjugated six-membered rings. Considering the success of intramolecular methyl-methyl coupling in circumcoronene synthesis from dodecamethyl hexa-perihexabenzocoronene, 33 we envision that the preplanarization might allow more efficient aromatization. Besides, a more reactive surface like Cu(111) is expected to achieve more sp 2 -hybridized carbons from the intramolecular methyl-methyl coupling.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Recently, intramolecular methyl-methyl coupling has been achieved to construct circumcoronene, a hexagonal NG with six zigzag edges. 33 However, the intramolecular coupling between two benzylic methyl groups has never been explored in GNRs, although it could potentially be developed as a powerful edge functionalization approach for structure engineering.…”
Section: Introductionmentioning
confidence: 99%
“…cyclodehydrogenation reactions on Au (111). In addition, a rationally designed synthetic route via the dehydrogenative coupling of adjacent methyl groups led to the ultrahigh-yield fabrication of circumcoronene on Cu (111) [41]. Furthermore, by a combination of STM/nc-AFM imaging and density functional theory (DFT) calculations, Zhong et al reported the onsurface synthesis of dibenzoperihexacenes (with and without tert-butyl (tBu) groups) and dibenzoperioctacene (with tBu groups, as shown in figure 3(a)) on Au (111) starting from tetranaphthyl-p-terphenyl and tetra-anthryl-p-terphenyl precursors, respectively [42].…”
Section: Fullerenes Cyclocarbons and Nanographenes In Small Sizementioning
confidence: 99%